Phytochemical constituents from leaves of Garcinia mangostana / Ahmad Kamal Ubaidillah Kambali - Kambali, Ahmad Kamal Ubaidillah (2015)
Throughout the whole Asia Pacific regions including Malaysia, Indonesia and also Thailand, it had been said to have the largest tropical ecosystem deprive of numerous numbers of plant with different type of species. It is estimated to have more than 12,000 species of higher plants which are available here in Malaysia, and from that number, about 10% of these plants are used to have medicinal purpose or medicinal use (Chin, et al., 2008) Pure compound from these plants are said to have been widely used as medicine for the past thousands of years and they were said to have such effect on curing numbers of disease or pains in the ancient times. The use and the medicinal properties of these plants are use and passed from generations to generations after throughout the history. In these recent study it have proven that most of these drugs are discovered from these medicinal plant from the point of which they have a potential for health benefits.